2010
DOI: 10.1111/j.1365-2605.2010.01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms, haplotypes and mutations in the protamine 1 and 2 genes

Abstract: Protamines are the most abundant nuclear proteins and alterations in their expression have been described in infertile patients. Also, protamine haplo-insufficient mice have been described as infertile. Therefore, the protamine 1 and 2 genes have been considered important candidates in different mutational studies. In this article, we review all published articles related to protamine gene mutations and report new data on mutations from patients and controls drawn from the Spanish and Swedish populations. Sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 77 publications
1
33
0
Order By: Relevance
“…Therefore, it is reasonable to hypothesise that the −190C>A polymorphism should result in significant changes in PRM1 geneexpression, bringing about significantly abnormal spermatozoa morphology and PRM1/2 content, as well as male infertility. An abnormal PRM1/PRM2 ratio (involving the appearance of a spermatozoa DNA fragment and increasing incidence of spermatozoa DNA fragmentation) has been clearly shown to be associated with male infertility (Jodar et al., ; Yu et al., ). Because male infertility involves a multifactorial aetiology, further studies are now required, involving larger sample sizes and stratification by environmental exposure, ethnic backgrounds or other risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is reasonable to hypothesise that the −190C>A polymorphism should result in significant changes in PRM1 geneexpression, bringing about significantly abnormal spermatozoa morphology and PRM1/2 content, as well as male infertility. An abnormal PRM1/PRM2 ratio (involving the appearance of a spermatozoa DNA fragment and increasing incidence of spermatozoa DNA fragmentation) has been clearly shown to be associated with male infertility (Jodar et al., ; Yu et al., ). Because male infertility involves a multifactorial aetiology, further studies are now required, involving larger sample sizes and stratification by environmental exposure, ethnic backgrounds or other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the trial sequential analysis, we found that the difference between individuals possessing a wild‐type genotype and individuals carrying a mutant allele represented a false negative. However, after considering a comprehensive list of factors, we believe that the precise location of the polymorphism markedly increases the risk of male infertility in some populations, as the mutation may lead to some key enzymes failing to cut and joint the PRM gene during spermatogenesis (Jiang, Sun, et al., ; Jiang, Zhang, et al., ; Jodar et al., ). Given the possibility that interactions are likely to be involved with other genes and environmental factors, we believe that future studies are crucial and should aim to recruit a large enough sample size to meet the requirements of statistical power calculations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protamines have a considerably high amount of amino acids carrying a positive charge which allow the creation of a tight package of genomic DNA in the spermatozoa (Oliva & Dixon, ; Retief et al, ). The chromosome 16 (16p13.2) has two expressed protamine genes protamine 1 ( PRM1 ) and protamine 2 ( PRM2 ), and they play a crucial role in the formation of a condensed nuclear genome (Jodar et al, ). Almost all changes in protamine genes may result in increasing the possibility for male infertility, as they have an important contribution in spermatogenesis (Tanaka et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In another recent study [7], based on massive genome sequencing, it was found that nucleosomes associated regions are significantly enriched in genes important for development, including imprinted genes, microRNAs, Hox genes, promoters and transcription developmental genes and signaling factors. It has also been shown that histone modifications (H3K4me2, H3K27me3) are reached at certain loci associated with developmental genes, and promoters associated with developmental genes are hypomethylated in the sperm, but are methylated during maturation [7,8]. …”
mentioning
confidence: 99%